Experimentos com o Arduino no ensino de Física: estudando conceitos científicos da Termologia - Pinheiro Junior, Jefferson Buonafina (2022)
Motivated by the application of Information and Communication Technologies (ICT) in the teaching of Physics, we developed the scripts for three experimental activities in Thermology using technological tools to be applied to high school students. The proposed experiments, whose data acquisition is automated through the application of thermal sensors and a computer-assisted Arduino board, can compare the heat conduction of different metals, show both qualitatively and quantitatively the difference between water and sand specifications when these materials are heated or cooled simultaneously by the same heat source and determine a thermal property of the specific heat. It is expected that students recognize that different materials have differences in thermal conductivity and understand the importance of the specific heat of water and sand in the formation of sea breezes. The experimental activities of our work, which establish a relationship between the scientific concepts discussed in the classroom and observable phenomena in nature, have the potential to increase the involvement of students in quality and quantity, promoting changes in their beliefs about Physics.